Lifetime history of concussion among children and adolescents with attention-deficit/hyperactivity disorder: examining differences stratified by age, medication status, and parent-reported severity - Maietta, Julia E.; Iverson, Grant L.; Cook, Nathan E. (Frontiers in Neurology, 2025)
IntroductionChildren and adolescents with attention-deficit/hyperactivity disorder (ADHD) are more likely to report a lifetime history of concussion compared to those without ADHD. Prior studies have predominantly relied on surveys of youth who self-reported their ADHD status (as opposed to parent report), examined samples with relatively narrow age ranges, and focused on youth athletes. It is unclear if ADHD severity or ADHD medication influences the association between ADHD and greater lifetime history of concussion. We investigated the association between parent-reported ADHD, ADHD severity, and medication status with parent-reported lifetime concussion history in children and adolescents ranging in age from 5 to 17, sampled from the United States general population.MethodsParent reported health data from 33,914 children and adolescents were selected from the 2021 National Survey of Children’s Health. Lifetime history of concussion, current ADHD diagnosed by a healthcare provider, and, for those with current ADHD, ADHD severity (mild or moderate/severe), and current ADHD medication status (yes/no) were reported by parents. A Mantel–Haenszel analysis was used to assess the associations between ADHD and lifetime concussion history across five age groups (ages 5–7, 8–10, 11–13, 14–15, and 16–17). Additional Mantel–Haenszel analyses were used to assess the associations between lifetime history of concussion and ADHD severity as well as medication status across five age groups.ResultsOverall, 6.2% of youth had a parent-reported history of concussion and 12.3% had parent-reported current ADHD. Twice as many youth with ADHD (10.6%) had a parent-reported history of concussion compared to youth without ADHD (5.6%). There were no differences in lifetime concussion history for those with mild (10.9%) versus moderate/severe ADHD (10.3%). Similarly, among those with ADHD, there were no differences in lifetime concussion history for those taking medication (9.9%) versus those not taking medication (11.6%).DiscussionConsistent with previous literature, youth with ADHD had greater lifetime concussion history than youth without ADHD (approximately twice the prevalence in those with ADHD). Contrary to our hypotheses among youth with ADHD, parent-reported ADHD severity and current medication status were not associated with lifetime concussion history.